Effect On Compatibility And Graphene On Shape Memory And Tensile Properties Of Polylactic Acid (PLA)/ Ethylene Vinyl Acetate (EVA) Blends - Rahmat, Nuruljannah (Universiti Sains Malaysia, 2022)
In this study, the thermo-responsive and tensile properties of polylactic acid (PLA)/ethylene co-vinyl acetate (EVA) blends were examined in relation to the compatibility of various blend compositions with varying vinyl acetate (VA) content and the incorporation of thermally conductive graphene nanoplatelet (GNP) fillers. Firstly, various compositions of PLA/EVA blends were melt blended with an internal mixer and then the blends were compression molded into the desired shapes. The shape memory properties such as shape fixity ratio (Rf) and shape recovery ratio (Rr) were investigated using a simple bending test. Both Rf and Rr increased with increasing EVA while at fixed amount of EVA, blend with VA content of 40% (EVA 40) showed higher Rf but lower Rr. Tensile strength and modulus decreased while elongation at break increased with increasing EVA content with EVA 40 blend indicated higher values due to better compatibility. After that, 1 wt% to 5 wt% of GNP were added to 70PLA/30EVA of different VA contents. PLA with EVA 19 blend showed in showed improvements in Rf, Rr, tensile strength and elongation at break of EVA 19 with 1 wt% and 3 wt% of GNP filler due to good interaction of the blend with GNP. Meanwhile, no significant trend of Rf and Rr and continuous reduction of tensile strength and elongation at break with increasing GNP content in the blend with EVA 40 due to reduction of interphase interaction. The presence low amount of graphene has greater effect on improvement in the tensile and shape memory properties of less compatible 70PLA/30EVA19 compared with more compatible 70PLA/30EVA40